Spontaneous Rupture of Hepatocellular Carcinoma - Ong, G. B. (1972)
Forty-two cases of ruptured hepatoma with intra-abdominal haemorrhage were seen over a period of eight years in the professorial surgical unit at the Queen Mary Hospital, Hong Kong. In all, 207 cases of liver cancer were seen during this period, giving an incidence of rupture of 14·5%. There were 37 men and five women. The clinical features were the sudden onset of pain with shock and the presence of blood in the peritoneal cavity. The diagnosis was made before operation on suspicion and by a process of elimination. In cases of doubt paracentesis abdominis was performed to determine whether there was blood in the peritoneal cavity. Treatment was directed to control of haemorrhage and resection. The prognosis, although extremely poor, is no worse than the hepatocellular carcinoma that has not ruptured. There was one long-term survivor—a patient who had undergone an extensive resection. The man was alive and well after more than five years.